Main parameters of extensive air showers at mountain altitudes - Sadykov, Т.Х.; Makhmet, Х.К.; Novolodskaya , О.А.; Piscal, В.В.; Argynova, А.Х.; Argynova, К.А.; Almenova, A.M.; Zhukov, В.В.; Osemuk, В.И. (Recent Contributions to Physics, 2024)
In high-energy physics one of the main directions is extensive air showers (EAS). This phenomenon currently remains poorly studied: scientists do not know the nature of their occurrence, mechanisms of their formation in the higher layers of the atmosphere, etc. In this paper, the main characteristics of air showers and their main properties were described. The basis of EAS research was formed by numerous experiments conducted at the Hadron-55 complex facility. The showers were recorded and processed by the ionization calorimeter method, the essence of which is to measure energy of EAS by the total ionization of particles. This calorimeter with iron and lead absorbers provides high accuracy of measurements, the experimental error of which is only 10%. Experimental data were processed by a program developed in C++. The experiments showed that the most common particles in the showers are electron-photon and hadronic components. Their share is 95-98% of the particles in the shower stem. The program processed 8717 showers for a time equal to 485 hours. The analysis of the energy range of the registered showers confirms the theory of their galactic origin. Also, the calculation of the main parameters makes it possible to carry out further studies of EAS in a more extended form.